Regioselective Synthesis of Polyfluoroalkyl Substituted 6, 7‐Dihydrobenzisoxazolones. (6th June 2018) - Khlebnicova, Tatyana S.; Piven', Yurii A.; Isakova, Veronica G.; Baranovsky, Alexander V.; Lakhvich, Fedor A.; Sorochinsky, Alexander E.; Gerus, Igor I.
Abstract : Regioselective methods for synthesis of hitherto unreported both 6, 7‐dihydro‐1, 2‐benzisoxazol‐4(5 H )‐ones and 6, 7‐dihydro‐2, 1‐benzisoxazol‐4(5 H )‐ones with perfluoroalkyl or halogenodifluoromethyl substituents have been developed. 3‐Polyfluoroalkyl‐6, 7‐dihydro‐1, 2‐benzisoxazol‐4(5 H )‐ones were prepared by the cyclocondensation of 2‐polyfluoroalkanoylcyclohexane‐1, 3‐diones with hydroxylamine. The regioisomeric 3‐polyfluoroalkyl‐6, 7‐dihydro‐2, 1‐benzisoxazol‐4(5 H )‐ones were synthesized by the transformation of 2‐polyfluoroalkanoylcyclohexane‐1, 3‐diones into their vinylogous chlorides, followed by the interaction of obtained crude 3‐chloro‐2‐polyfluoroalkanoyl‐2‐cyclohexen‐1‐ones with sodium azide in dimethylformamide. Abstract :